DINAMIKA KELOMPOK TANI PADA PROGRAM KEBUN BIBIT RAKYAT (KBR) DI KABUPATEN PINRANG, SULAWESI SELATAN - Ayu Rahayu; Asar Said Mahbub; Makkarennu Makkarennu1 (Jurnal Penelitian dan Pengembangan Agrokompleks, 2018)
Development of Community nursery (Kebun Bibit Rakyat: KBR) is one of the programsupported by national government involving farmer groups in an effort to support the functionand carrying capacity of land and efforts to improve the welfare of the community. Thedynamics of farmer groups is crucial to the success of this KBR program. This study aim toidentify the dynamics of Farmers Group KBR. This research was focused at Sylva Lestarifarmer group in Duampanua Subdistrict, Pinrang Regency, South Sulawesi. Methods of datacollection are direct observation and interview by using interview guide (semi structuredinterview) to farmer group member. Group dynamics are identified by elemental elements:objectives, structures, institutions, development and coaching, cohesiveness, atmosphere andgroup effectiveness. The number of respondents is 19 people. Data analysis used qualitativedescriptive method. The results showed that the dynamics of farmers group KBR Sylva Lestaribased on group dynamics elements dynamically categorized (96.2%). This shows that theinteraction between members in the group goes well so that the goals set can be realized